ANTI-BACTERIAL EFFECTIVENESS OF CHITOSAN OF PAPUYU FISH (Anabas testudineus) AGAINST BACTERIA Streptococcus mutans - Titien Marwah Sadsyam; Muhammad Yanuar Ichrom Nahzi; Juli Harnida Purwaningayu (FKG ULM, 2024)
Background: Streptococcus mutans is one of the main bacteria that cause dental caries by demineralized hard tissues of the teeth. People can use natural ingredients to reduce the number of Streptococcus mutans microorganisms, that is chitosan papuyu fish scales (Anabas testudineus). Purpose: The purpose is to analyze the antibacterial effectiveness of chitosan from papuyu fish scales (Anabas testudineus) against Streptococcus mutans bacteria based on the values of the MIC (Minimum Inhibitory Concentration) and MBC (Minimum Bactericidal Concentration). Methods: This is an experimental study with posttest only with a control group design using 30 samples of chitosan papuyu fish scales (Anabas testudineus) grouped into 6 treatment groups and 5 samples repetitions. The treatment groups were chitosan papuyu fish scales (Anabas testudineus) with concentrations of 25%, 50%, 75%, and 100%, 0.2% chlorhexidine as a positive control, and aquades as a negative control. Calculation of absorbance using a UV-VIS Spectrophotometer Biobase BK-D560 for MIC and Streptococcus mutans bacterial colonies were visualized with a colony counter for MBC. Results: The results of the Kruskal Wallis test for MIC and MBC of papuyu fish chitosan concentrations of 25%, 50%, 75%, and 100% obtained significant results of p=0.00, which means p<0, 05 and showed a significant difference between treatments. Conclusion: There are differences in the effectiveness of MIC and MBC chitosan of papuyu fish scales (Anabas testudineus) at concentrations of 25%, 50%, 75%, 100%, chlorhexidine gluconate 0.2% (positive control), and aquadest (negative control).